The musical effects in the poem of : Emrio‘ Alqays - Mohammed, Ibrahim Abdullah Ibrahim; Fadlallah, Mohamed Abdullah Mohamed; Ahmed, Gamal El Din Ibrahim Abdel Rahman (Journal of Humanities & Social Sciences, 2017)
This study is about the "musical influences in the poem  of the poet: Emro Algays , by description, analysis and interpretation, in addition    to the grammatical, morphological, linguistic, rhetorical,  and rhythmic influences followed by their rhythms , melodies, and their effect in forming the melodic wave in about twenty segments . The descriptive analytical method; is adopted in the study,  for it can     describe  vividly and analyze deeply  the different rhythmic phenomena, highlighting the aesthetics of language and artistic images. The end-product of the study unveiled the following fruits:                                                                      The poet adopted (Bahr al-Tawil II)(one of the Arabic poetry rules made by the linguistic scholar – Alkahleel Bin Ahmed Alfrahidi) to express his deep passionate emotions and his violent adventures in chasing and Fishing .2- The narrators agreed to the authenticity  of the poem and did not differ only in four verses .. The poem  eloquence  percentage arrived at 46%, while the proportion of  the mental emotion  - according to the theory of Buthee Man - is about 2.39%.3- The two  vowel segments of the poem are equal in all verses of the poem at a rate of (14 segments) for each section.Verse 4 which read as follows: You see the deer's remains  in the space and valleys like peppercorn , this vers is thought to be the most poetic verse for  the quietness  and pacific tune due to the notions of the of letters. The verse 76  is thought to the most eloquent verses due to the concentration of the letters notion which called (Flashing). As for the verses 14 and 74 are the most eloquent verses.    The verse 54 which gives a vivid details to the horse, in all situations, has got a sweetness of the rhythm, the melody and the attraction of the music, the most complete of the songs ,with no dispute on its authenticity.
Keywords: influences; music; Imru' al-Qais